Unclassifiable renal carcinoma with medullary phenotype and SMARCB1 deficiency: case report - Mehanna, Samya H.; Ronkoski, Thiago Gabriel; Machado, Cassiano; Wolff, Lucas S.; Cavalli, Alexandre C.; Hota, Thiago; Koleski, Fernando C. (Frontiers in Urology, 2025)
BackgroundRenal medullary carcinoma (RMC) is an aggressive tumor representing less than 0.5% of renal cell carcinomas (RCC), and it is considered rare. When it occurs, patients typically have sickle cell trait, sickle cell disease, or an associated hemoglobinopathy, which is a necessary characteristic for diagnosis. Additionally, RMC is characterized by the inactivation of alterations in the SMARCB1 (INI1) tumor suppressor gene, resulting in the loss of INI1 immunohistochemical expression. However, there are tumors reported in the literature with the same morphological and phenotypic characteristics as RMC but without hemoglobinopathy, referred to as “unclassified RCC with medullary phenotype.”Case reportWe present the 13th case of unclassified renal cell carcinoma with a medullary phenotype in a 20-year-old woman. The patient was admitted with complaints of macroscopic hematuria, with no significant findings on physical examination. Diagnostic investigation included a computed tomography urogram, which revealed a hypovascular oval image with central cystic/necrotic areas in the middle third of the right kidney, measuring 32 mm, suggesting a possible diagnosis of an infected renal cyst. Subsequent magnetic resonance imaging showed findings consistent with an atypical presentation of primary neoplasia in the differential diagnosis, prompting a renal biopsy for case definition. Histopathological analysis revealed a high-grade infiltrative epithelioid neoplasm. Immunohistochemistry showed positivity for PAX8 and loss of INI-1 expression. No hemoglobinopathies were identified in the patient, in this context, the neoplasm is appropriately classified as unclassified renal cell carcinoma (RCC) with medullary phenotype and SMARCB1 deficiency. The instituted therapy consisted of right radical nephrectomy with retroperitoneal lymphadenectomy, with nodal metastases detected.ConclusionGiven the rarity of unclassified RCC with a medullary phenotype, continuous documentation and analysis of individual cases not associated with sickle cell trait are crucial to understanding its behavior, prognosis, and potential therapeutic approaches, considering its aggressiveness and high metastatic potential.